A critical overview of the current myofascial pain literature – January 2016. Issue 1 (January 2016) - Dommerholt, Jan; Finnegan, Michelle; Grieve, Rob; Hooks, Todd
Summary: Reflecting on the past year, the number of publications on myofascial pain continues to increase in a steady rate. The current review includes 30 basic and clinical studies, case reports, reviews, and reports from fifteen different countries about trigger points (TrP), myofascial pain (MP), dry needling (DN) and other related interventions. We are pleased that during 2015 this article made the top 15 of most downloaded articles as many as three times! In general, the quality of published papers is improving as well. Nevertheless, several papers included in this overview, mention the application of "ischemic compression", which is a questionable concept in the context of TrP inactivation. As we have outlined previously, in the current thinking about myofascial pain, TrPs feature significant hypoxia and a lowered pH (Ballyns et al., 2011; Shah and Gilliams, 2008), and attempts to induce more ischemia would be counterproductive. Already in 1999, Simons, Travell and Simons changed the terminology from ischemic compression to TrP compression (Simons et al., 1999) and we recommend that contemporary researchers and clinicians adopt the new terminology and stop using the term "ischemic compression."